Profit and Passion : Transactional Sex in Colonial Mexico - Germeten, Nicole von (Book collections on Project MUSE., 2018)
"This book recounts four centuries of the history of women labeled public women, whores, and prostitutes in New Spain's archival records and works of literature from Spain and Mexico. Performing conventional gender roles, women resisted the archival inscription of these labels, so this complex story of multi-layered viceregal sex work acknowledges the ambiguities and limitations of documenting the history of sexuality via written sources. The elusive, ever-changing terminology for prosecuted women in the early modern Iberian world, voiced by kings, jurists, magistrates, inquisitors, and bishops, as well as disgruntled husbands and neighbors, foreshadows the increasing regulation, criminalization, and polarizing politics of modern global transactional sex. Key themes include: the history of the word "prostitute/prostitution," narratives presented by women in a court setting, the creation of a victim narrative by defendants and prosecutors, legal history, and the importance of the economic and familial context in shaping sexual transactionality. Sources used come from the archives of police, church, and inquisitorial investigations. Interpretations are shaped by archival and sex work activism theories"--Provided by publisher.